ChemInform Abstract: Indium(III)‐Catalyzed Reductive Monoalkylation of Electron‐Rich Benzenes with Aliphatic Carboxylic Acids Leading to Arylalkane Derivatives. Issue 31 (August 2015) - Moriya, Toshimitsu; Takayama, Kentaro; Konakahara, Takeo; Ogiwara, Yohei; Sakai, Norio
Abstract A one‐pot monoalkylation of benzene derivatives with aliphatic carboxylic acids having a variety of substituents with a combination of InI3, hydrosilane, and molecular iodine is reported.